Research on the Influence of New High-performance Fiber Materials in Tennis Sports - Wenxian Fan (Forest Chemicals Review)
The rapid development of modern materials and their processing technology is the basis for improving the performance of sports equipment such as bicycles, skateboards, rackets, and clubs. Taking tennis as an example, the article analyzes the impact of new high-performance fiber materials on tennis and other sports. Dimensions generally have the characteristics of high strength, light weight, and good wear resistance. Therefore, this can help sports equipment to further improve its own performance. Quality, especially in the development of sports equipment at this stage, the wide application of fiber materials has become a common material used in the entire sports products. In order to obtain a more solid and elastic carbon fiber tennis racket, we have proposed a optimization method of the adhesive used for the bonding of carbon fiber tennis rackets. The advantages and applications of carbon materials in sports equipment, and looked forward to the application prospects of carbon materials in the field of sports equipment in the future.